Efecto de la densidad de plantación sobre las propiedades de tracción y clivaje perpendicular en sentido radial y tangencial de madera de madera de Eucalyptus grandis Hill (ex Maiden) de 11 años de edad - Barth, Sara Regina; Bragañolo, Adelaida; Keller, Aldo Esteban; Feldman, Alexis; Primo, Agustín; Morel, Matías; Winck, Rosa Ángela; Aquino, Diego Rolando; Knebel, Otto Eduardo (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2023)
When deciding on the silvicultural management of forest plantations, it is important to consider their production objective. Different planting densities lead to variations in the dimensions of individual trees and, consequently, the logs to be obtained, as growth is influenced by spacing. This results in differences in the properties of the wood to be obtained. Analyzing the tensile and cleavage efforts in the radial and tangential directions in juvenile Eucalyptus grandis wood, no significant differences were found between treatments, but differences were observed between the first and second logs to be sawn.